2016
DOI: 10.1016/j.biortech.2015.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical conversion of sugarcane straw hemicellulosic hydrolyzate supplemented with co-substrates for xylitol production

Abstract: Biotechnological production of xylitol is an attractive route to add value to a sugarcane biorefinery, through utilization of the hemicellulosic fraction of sugarcane straw, whose availability is increasing in Brazil. Herein, supplementation of the sugarcane straw hemicellulosic hydrolyzate (xylose 57gL(-1)) with maltose, sucrose, cellobiose or glycerol was proposed, and their effect as co-substrates on xylitol production by Candida guilliermondii FTI 20037 was studied. Sucrose (10gL(-1)) and glycerol (0.7gL(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…Moreover, the decrease in acid concentration promoted the neutralization of broth, pH was increased from 5.63 up to a value of 6.78. Acetic acid consumption by other yeasts such as C. guilliermondii and S. stipitis has been reported . As stated by Felipe et al .…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Moreover, the decrease in acid concentration promoted the neutralization of broth, pH was increased from 5.63 up to a value of 6.78. Acetic acid consumption by other yeasts such as C. guilliermondii and S. stipitis has been reported . As stated by Felipe et al .…”
Section: Resultsmentioning
confidence: 77%
“…reported: Y P/S = 0.75 g g −1 , Q P = 0.48 g L −1 h −1 and η = 81.7% during growth hemicellulosic hydrolysate from sugarcane bagasse. Hernandez‐Perez et al . obtained values of Q P = 0.77 g L −1 h −1 and η = 70.0% when this yeast was grown in hemicellulosic hydrolysate from sugarcane straw.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that 10 g/100 mL solid/liquid ratio and 1.25 % sulfuric acid would be appropriate for initial preparation of the hydrolysate before detoxification and concentration. Various lignocellulosic residues have been reported to be used for xylitol production, some of which were corncob (Cheng et al 2009; Kamat et al 2013; Ramesh et al 2013) sugarcane straw (Hernández-Pérez et al 2016), cotton stalks (Akpinar et al 2011), grape marc (Salgado et al 2012), cashew apple bagasse (Albuquerque et al 2015a), wheat straw (Canilha et al 2005), wood sawdust (Rafiqul and Mimi Sakinah 2012), vine trimming wastes (Rivas et al 2007), and rice husks (Rambo et al 2013). Chestnut shells have been used in some studies for different purposes (Aires et al 2016).…”
Section: Resultsmentioning
confidence: 99%